Fendas em classe V de resinas Bulk Fill: uma avaliação em microscopia eletrônica de varredura - Righes, Danielle Zorzo (2019)
The aim of this in vitro study was to evaluate under scanning electron microscopy (SEM), the gap formation due to the shrinkage stress of a conventional resin (Filtek Z350XT [3M ESPE]) and two types of bulk-fill resins (Filtek Bulk Fill [3M ESPE] and Opus Bulk Fill [FGM]) along the margins of class V restorations. On each of the 36 extracted human non-carious molar teeth, class V cavities were prepared on the medium third of buccal and lingual surfaces, which were divided into six groups (n = 6), according to the restorative technique: incremental and unique insertion technique. After restoration, each molar was cut in half in the buco-lingual direction between the two restorations, resulting in two specimens per molar. The specimens were evaluated in SEM and the data were submitted to one-way ANOVA and Tukey test, at a significance level of 5%. The gaps were measured at three different points from the all walls to the restoration with 250x magnification to determine the mean of each wall. All the composites resins (Filtek Z350 XT, Filtek Bulk Fill and Opus Bulk Fill) tested individually in the unique and incremental insertion techniques did not present statistical difference, however, Filtek Bulk Fill composite when used in the technique recommended (unique insertion) shows better result compared to Z350 XT in the incremental insertion technique. All the groups had a predominance of gingival wall gaps being the most critical region.